2004
DOI: 10.1074/jbc.m313615200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hepatic Metabolism of 7-Ketocholesterol by 11β-Hydroxysteroid Dehydrogenase Type 1

Abstract: The role of 11␤-hydroxysteroid dehydrogenase type 1 (11␤-HSD1) in the local activation of the glucocorticoid receptor by converting inactive 11-ketoglucocorticoids to active 11␤-hydroxyglucocorticoids is well established. Currently, 11␤-HSD1 is considered a promising target for treatment of obese and diabetic patients. Here, we demonstrate a role of 11␤-HSD1 in the metabolism of 7-ketocholesterol (7KC), the major dietary oxysterol. Comparison of recombinant 11␤-HSD1, transiently expressed in human embryonic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 46 publications
2
53
1
Order By: Relevance
“…This conversion was more than double that observed when CS substrate concentration was 25 times higher, suggesting inhibition by the substrate (CS) or its product (DHC). These results suggest that the conversion of 7α-OH-DHEA to 7-oxo-DHEA is catalyzed by low-affinity/high capacity enzyme(s), while the oxidation of CS to DHC may involve high-affinity/low capacity enzyme (s) as has been described for 11βHSD2 [29].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…This conversion was more than double that observed when CS substrate concentration was 25 times higher, suggesting inhibition by the substrate (CS) or its product (DHC). These results suggest that the conversion of 7α-OH-DHEA to 7-oxo-DHEA is catalyzed by low-affinity/high capacity enzyme(s), while the oxidation of CS to DHC may involve high-affinity/low capacity enzyme (s) as has been described for 11βHSD2 [29].…”
Section: Resultsmentioning
confidence: 72%
“…The oxidation of 7-hydroxycholesterol and CS by this purified enzyme was inhibited by CBX. Subsequently, human, rat, and mouse 11βHSD1 have been reported to possess a 7β-hydroxycholesterol dehydrogenase activity that allows interconversion between 7-ketocholesterol and 7β-hydroxycholesterol with similar efficiency as observed for GC [28,29]. In the current studies, pig kidney mitochondria oxidized 7α-OH-DHEA in the presence of either NAD + or NADP + at a very low rate (approx.…”
Section: Discussionmentioning
confidence: 88%
“…11 ␤ -HSD1 has broad substrate specifi city and metabolizes, besides 11-ketoglucocorticoids, several oxidized endogenous steroids and sterols (19)(20)(21)(22)(23)(24)(25). Performing in vitro experiments, we recently identifi ed a novel role for human 11 ␤ -HSD1 in the metabolism of the secondary bile acid 7-oxoLCA ( 26 ).…”
Section: Impact Of Bile Acids On the Interconversion Of Glucocorticoimentioning
confidence: 99%
“…To assess species-dependent differences in the 11 ␤ -HSD1-dependent metabolism of 7-oxoLCA, we transiently transfected HEK-293 (human embryonic kidney-293) cells [cultured in Dulbecco's Modifi ed Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 50 units/ml penicillin, 50 g/ml streptomycin and 2 mM glutamine] with plasmids coding for human, rat, mouse, hamster, canine, and guinea-pig 11 ␤ -HSD1 as described previously ( 23,29,30 ). At 48 h posttransfection (jetPRIME, Polyplus transfection, Illkirch, France) cells were detached and centrifuged, and pellets were stored at Ϫ 80°C.…”
Section: Reduction Of 7-oxolca By Recombinant 11 ␤ -Hsd1 From Variousmentioning
confidence: 99%
“…Nevertheless, an accumulation of orally administered 7-ketocholesterol was observed in rats treated with the inhibitor carbenoxolone. [44] More recently, we found that 11β -HSD1 metabolizes 7-ketodehydroepiandrosterone and 7-ketopregnenolone, suggesting a role not only in the detoxification of oxidized cholesterol from food but also of oxidized steroid hormone metabolites. [49] …”
Section: Compounds Inhibiting 11β -Hsd1mentioning
confidence: 99%